Mastitis in beef cattle - Tetiana Holumbiiovska; Roman Bokotko; Grzegorz Dejneka (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Mastitis and udder infections pose significant health challenges for cattle, including beef breeds, although less commonly than in dairy herds. This study aims to explore mastitis' etiology, risk factors, diagnosis, and treatment in beef cows, focusing on their specific rearing and breeding conditions. Beef cattle are typically reared for calf production, and calves remain with their mothers until weaning, relying on natural suckling. Factors contributing to mastitis in beef cows include calf-related behaviors, environmental conditions, and cow-specific factors. Calves may introduce pathogens through frequent suckling, while environmental factors like wet and dirty bedding and insect infestations increase infection risk. Cow factors such as udder morphology, lactation phase, and age also influence susceptibility to mastitis. Bacterial infections, primarily caused by Staphylococcus and Streptococcus species, are the leading cause of mastitis in beef cows. The disease is often subclinical, making diagnosis challenging due to the limited contact between farmers and cows, as beef cattle are typically kept on pasture. Clinical signs, when present, include udder swelling, pain, and reduced milk production. Treatment mainly involves antibiotic administration, with local and systemic treatments depending on infection severity. However, many subclinical cases remain untreated. Early detection and treatment are crucial to prevent chronic conditions that reduce cow productivity and calf growth.